Filosofi Tri Kaya Parisudha Memoderasi Pengaruh Persepsi Karyawan Mengenai Whistleblowing System Dan Pengendalian Internal Terhadap Pencegahan Fraud (Studi Empiris Pada BUMDes di Kecamatan Banjar, Kabupaten Buleleng) - Alit, Ngurah; Devi, Sunitha (Jurnal Akuntansi Profesi, 2021)
This study aims to determine the effect of employee perceptions of the whistleblowing system and internal control on fraud prevention; Tri Kaya Parisudha's philosophy can moderate the relationship between employee perceptions of the whistleblowing system and internal control over fraud prevention. This type of research is quantitative research. The population used is all employees at BUMDes in Banjar District. The sampling technique used the census method, with a sample of 37 respondents. Data analysis in this study used descriptive analysis, data quality test, classical assumption test, and hypothesis testing with the help of the SPSS version 23.0 program. The results show (1) employee perceptions of the whistleblowing system have a positive and significant effect on fraud prevention, (2) internal control has a positive and significant effect on fraud prevention, (3) the tri kaya parisudha philosophy can moderate the relationship between employee perceptions of the whistleblowing system and fraud prevention; and (4) the tri kaya parisudha philosophy can moderate the relationship between internal control and fraud prevention.Keywords: whistlebowing system, internal control, fraud prevention, tri kaya parisudha